Noninvasive screening of extracranial carotid disease: duplex sonography with angiographic correlation. - Clark, W M; Hatten, H P (American Journal of Neuroradiology, 1981)
Initial experience with a pulsed Doppler device coupled to a high resolution real-time sonographic scanner for noninvasive evaluation of extracranial carotid disease is reported. The primary objective was to evaluate patients with asymptomatic cervical bruits and/or equivocal histories of transient cerebral ischemia to determine which of them required further study with angiography. An assessment of the degree of extracranial carotid stenosis as well as the severity of atheromatous plaque formation was made and subsequently compared with the findings at angiography. During a 455 day period, a total of 501 patients were examined. In 150 arteries with complete angiography, correlation disclosed the noninvasive duplex technique to be 92% accurate in predicting which arteries would be significantly diseased. It is proposed that careful sonographic investigation of the extracranial carotid system is a safe and useful screening test for certain patients at risk for cerebrovascular accident.